Renewable energy, trade performance and the conditional role of finance and institutional capacity of sub-Sahara African countries - Opeyemi Akinyemi; Uchenna Rapuluchukwu Efobi; Simplice Asongu; Evans Osabuohein (African Governance and Development Institute (AGDI), 2019)
The paper investigates the dynamic relationship between renewable energy usage and trade performance in sub-Saharan Africa (SSA), while considering the conditioning role of corruption control, regulatory quality, and the private sector access to finance. Focusing on 42 SSA countries for the period 2004-2016, and engaging the System generalized method of moments (GMM) technique for its estimation, this study found a negative relationship between renewable energy usage and the indicators of trade performance. However, with corruption control, improved regulatory framework, and better finance for the private sector, there are potentials for a positive net impact of renewable energy usage on manufacturing export. For renewable energy and total trade nexus, we find that improved regulatory framework and better finance for the private sector are important conditioning structures. These findings are significant because they highlight the different important structures of SSA countries that improve the effect of renewable energy use on trade outcomes. For instance, the consideration of the financial, institutional and regulatory frameworks in SSA countries in conditioning the renewable energy-trade nexus stipulates a clear policy pathway for countries in this region as the debate for transition to the use of renewable energy progresses.
Keywords: C5; F1; Q4; Q5; 330; Environment; Green growth; Trade performance; Pollution; Renewable energy; sub-Saharan Africa